Community response towards toxic and hazardous substances the Bulacan, Philippines experience - Mendoza, M. E. T.; Jimena, C. G.; Visco, E. S.; Amparo, J. S.; Mendoza. M. D. (2003)
The study was conducted to determine the knowledge, attitude and perception of the people in Meycauayan and Marilao towards toxic and hazardous substances present in their respective communities. Results showed that the respondents were aware of the hazards of the toxic substances used in gold smelting, leather tanning and lead recycling. Many of the respondents attributed the disease they suffer like skin diseases, coughs, and cold, lung problems and others to exposure to toxic chemicals and fumes from the industries mentioned. However, respondents from barangays chosen to represent gold smelting, have attitudes reflecting undecidedness since they recognized the economic distribution of the industry in the area. The same results were found in the attitudes towards leather tanning. However, respondents were very much willing to participitate in any information campaign on environment and heath issues to make the people aware of the continued hazards caused by these industries. While the grim effect of environmental pollution may have probably sunk in the consciousness of the people in the study areas as shown by their concerns about their health, they apparently seem to be more concerned about the economic condition they might suffer if they do not have these industries in their cases.
Keywords: Hazardous substances; Perception